Enlarging moment and regulating orientation of buried interfacial dipole for efficient inverted perovskite solar cells - Yang Peng; Yu Chen; Jing Zhou; Chuan Luo; Weijian Tang; Yuwei Duan; Yihui Wu; Qiang Peng (Nature Communications)
Abstract Carrier transport and recombination at the buried interface of perovskite have seriously restricted the further development of inverted perovskite solar cells (PSCs). Herein, an interfacial dipolar chemical bridge strategy to address this issue is presented. 2-(Diphenylphosphino) acetic acid (2DPAA) is selected as the linker to reconstruct the interfacial dipole, which effectively enlarges the interfacial dipole moment to 5.10 D and optimizes to a positive dipole orientation, thereby accelerating vertical hole transport, suppressing nonradiative recombination and promoting the perovskite crystallization. The champion inverted device yields a high power conversion efficiency (PCE) of 26.53% (certified 26.02%). Moreover, this strategy is extended to the wide-bandgap perovskite and large-area devices, which delivers high PCEs of 22.02% and 24.11%, respectively. The optimized devices without encapsulation also demonstrate great long-term shelf and operational stability. Our work highlights the importance of interfacial dipole moment and orientation at the buried interface to realize efficient and stable inverted PSCs.